The Global Studio - Incorporating Peer-Learning into the Design Curriculum - Ghassan, Aysar; Bohemia, Erik (FormAkademisk, 2015)
In ‘tutor-led’ design education, lecturers reside at the centre of teaching & learning activities. We argue that tutor-led design education does not prepare graduates sufficiently for working in highly complex professional capacities. We outline an alternative learning environment named the Global Studio in which lecturers are more ‘distant’ in pedagogical activities. This ‘distance’ opens up learning spaces which expose students to complex project situations in preparation for professional working life. Global Studio projects are ‘student-led’ and contain explicit opportunities for peer tutoring to ensue. Feedback indicates that learners benefitted from engaging in peer tutoring. However, many students struggled with making important decisions when operating outside of the tutor-led learning environment. To maximise their benefit, we argue that student-led projects featuring peer-tutoring should be scaffolded throughout design programmes to provide students with a sufficient level of exposure to this mode of learning. Image by artist Malcom Jones. http://www.malcomjones.com/index.htm